And Deliver Us to Segmentation: The growing appeal of the niche news audience. (7th February 2018) - Nelson, Jacob L.
Abstract : Non-profit news publishers, a small but growing piece of the news media environment, often explicitly attempt to build strong ties with their audiences. Many assume this approach differs from that of legacy newsrooms, which have historically kept the audience at arm's length. In this article, I argue that this distinction has blurred. In-depth interviews with reporters and editors at a daily newspaper (The Chicago Tribune) and a local news non-profit (City Bureau) reveal that: (1) both organizations are pursuing a more collaborative relationship with their audiences; and (2) this pursuit is ill-suited for the traditional mass audience approach to news production. I conclude that journalists aspiring to work more closely with the audience find greater success when that audience is narrow to begin with.